Estado hídrico, resposta iônica e produção de cultivares de sorgo sob estresse hídrico e salino - Silva, Rodrigo Rafael da (Universidade Federal Rural do Semi-Árido, 2021)
Sorghum is a crop with high production potential for dry regions, as it is tolerant to water deficit and adapts well to salt stress conditions. Thus, the objective of the research is to evaluate the influence of water and saline stresses provided by different blades and salt concentrations in the irrigation water on nutrient content and sorghum biomass production of cultivars BRS Ponta Negra and IPA SF-15 under climatic conditions of the semiarid region. Two experiments were conducted simultaneously from September to December 2019, in the experimental area located at the Cumaru site, municipality of Upanema-RN. Experiment I: Cultivate BRS Ponta Negra and Experiment II: Cultivate IPA SF-15. The adopted design was randomized blocks in a factorial scheme (4 x 4), with 4 salt concentrations (1.5; 3.0; 4.5 and 6.0 dS m -1) and 4 irrigation depths (51.3; 70.6; 90.0 and 118.4 % of ETc), with 3 repetitions. Soil pH, CEes and RASes of the soil were evaluated. For the production data, two harvests were carried out for BRS Ponta Negra at 68 and 90DAP and Cultivar IPA SF-15 at 76 and 95DAP, evaluating the percentage of plant with clusters, percentage of dry weight, plant yield, total dry weight and fresh weight of the stem. In the diagnosis sheet, the nutrient contents were determined; sodium, potassium, calcium, magnesium, phosphorus and chlorine. The data were interpreted through the analysis of variance using the F test and applying regression analysis, polynomial models for slides and salinity at the 5% level of significance. The results found show that there is no interaction between salinity and irrigation depths under the production of sorghum plants for the analyzed variables. The salinity of the irrigation water caused an increase in the electrical conductivity of the soil solution, which was reduced with the application of irrigation depths. Sorghum plants were more sensitive to water deficit in the flowering phase than in the final development phase. O sorgo BRS Ponta Negra e IPA SF-15 não tem perda de produção quando é irrigado com água de CE de até 6,0 dS m-1
Keywords: Sorghum bicolor (L.) Moench; Concentrações sais; Déficit hídricos; Teores de nutrientes; Rendimento; Sorghum bicolor (L.) Moench; Salt concentrations; Water Deficit Nutrient Content; Yield; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO